Improving performance of proton ceramic electrolysis cell perovskite anode by Zn doping. Issue 12 (15th June 2023) - Cheng, Xiaojie; Li, Guangdong; Ren, Rongzheng; Xu, Chunming; Qiao, Jinshuo; Sun, Wang; Wang, Zhenhua; Sun, Kening
Abstract: As an important renewable energy, hydrogen energy becomes an important part of the future energy system. Proton ceramic electrolysis cell (PCEC) enables the efficient, clean, large-scale preparation of hydrogen, which is a new type of energy conversion device, attracting the attention of many researchers. Sr2 Fe1.4 Zn0.1 Mo0.5 O6-δ (SFZM) anode materials were developed to investigate the effect of B-site doping of Zn on the electrochemical properties of the Sr2 Fe1.5 Mo0.5 O6-δ (SFM) materials. The results reveal that the doping of Zn increases the concentration of oxygen vacancies and improves the electrocatalytic activity, which in turn improves the performance of the material. A current density of 408 mA cm −2 has been achieved at 1.3 V when the SFZM-based single cell was operated in an electrolysis mode (50% H2 O in air) at 600 °C, higher than SFM-based single cells (286 mA cm −2 at 1.3 V). In addition, the SFZM-based single cell exhibited good durability in a stability test at an electrolysis current density of 408 mA cm −2 . This work confirms that SFZM is a promising material for proton ceramic electrolysis cell anode.